Ancient and early medieval kingdoms of the Pamir region of Central Asia - Zoolshoev, Muzaffar Zoirshoevich, author.
1 online resource
Keywords: This focused study is one of the few analytical resources in English that covers the ancient and early medieval history of one of the least studied areas of the vast mountainous Pamir region of Central Asia: Shughnn. The book brings together scattered fragments of information from a wide range of early Greek, Chinese, Persian, and Arabic sources, the accounts of early European travellers and the scholarly contributions of Soviet and post-Soviet authors, as well as personal accounts and oral history material from the region. Drawing on historical, archaeological, linguistic, and ethnographic data, it provides a holistic overview of the kingdom of Shughnn. It also attempts, for the first time, to identify and locate the town of Khn, which the Chinese historical chronicle, the Tng Sh (Book of the Tang Dynasty, 618-907 CE) describes as the first capital' of Shughnn. Many archaeological sites are examined and offered as potential candidates for the location of the town of Khn, providing a foundation for future archaeological and ethnolinguistic research in the area. Ancient and Early Medieval Kingdoms of the Pamir Region of Central Asia: Historical Shughnn and its Lost Capital is suitable for students, scholars, and historians studying ancient and early medieval Central Asia, particularly the Pamir region, as well as those interested in Central Asian history and archaeology more broadly.